2021
DOI: 10.1101/2021.02.05.429745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intraspecific trait changes have large impacts on community functional composition but do not affect ecosystem function

Abstract: Plant functional traits can provide a more mechanistic understanding of community responses to global change and effects on ecosystem functions. In particular, nitrogen enrichment shifts trait composition by promoting dominance of fast growing, acquisitive plants (with high specific leaf area [SLA] and low leaf dry matter content [LDMC]), and such fast species have higher aboveground biomass production. Changes in mean trait values can be due to a shift in species identity, a shift in species relative abundanc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 68 publications
0
9
1
Order By: Relevance
“…Our results suggest that patterns of disease can be strongly influenced by inter- and intraspecific variation in SLA, but relationships between SLA and biotic interactions are being increasingly recognized as multidirectional: not only can host pace-of-life influence biotic interactions but biotic interactions can reciprocally influence intraspecific variation in host pace-of-life. For example, across 101 species embedded in alpine communities, SLA decreased with increasing herbivory [101], within eight common tundra plant species, SLA increased when mammalian herbivory was excluded [102], and across 20 species in a biodiversity manipulation, fungicide application reduced SLA within species [103]. Together with the results of this study, these experimental results highlight the potential for important feedbacks between ITV and disease risk in host communities experiencing climate change.…”
Section: Discussionmentioning
confidence: 70%
“…Our results suggest that patterns of disease can be strongly influenced by inter- and intraspecific variation in SLA, but relationships between SLA and biotic interactions are being increasingly recognized as multidirectional: not only can host pace-of-life influence biotic interactions but biotic interactions can reciprocally influence intraspecific variation in host pace-of-life. For example, across 101 species embedded in alpine communities, SLA decreased with increasing herbivory [101], within eight common tundra plant species, SLA increased when mammalian herbivory was excluded [102], and across 20 species in a biodiversity manipulation, fungicide application reduced SLA within species [103]. Together with the results of this study, these experimental results highlight the potential for important feedbacks between ITV and disease risk in host communities experiencing climate change.…”
Section: Discussionmentioning
confidence: 70%
“…Meanwhile, these results also highlight the importance of intraspecific trait variations. Recent studies showed that intraspecific trait variations might be equal or greater than interspecific variations in determining community responses to biotic and abiotic environmental changes (Jessen et al, 2020; Pichon et al, 2022; Wang et al, 2022; Wilfahrt et al, 2020). Consistent with these studies, we found that the fungicide effect on plant community biomass was more related to intraspecific trait variations, rather than trait changes induced by abundance shifts (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Due to local adaptation or phenotypic plasticity, functional traits of plant individuals within one species can vary in response to environmental changes (Albert et al, 2011; Messier et al, 2010; Violle et al, 2012). Generally, nitrogen addition can increase plant individuals' height, leaf chlorophyll content, SLA and decrease LDMC, which are related to fast growth in resource‐rich conditions (Pichon et al, 2022; Wang et al, 2022; Wilfahrt et al, 2020). However, these intraspecific trait variations may increase the pathogen effect on plants because developing these fast‐growing traits often comes at the cost of reduced defense against natural enemies (Coley et al, 1985; Herms & Mattson, 1992; Züst & Agrawal, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, we found overall weak diversity-mediated indirect effects on stability. A few other studies also show that traits are poor predictors for ecosystem properties including productivity and its stability (van der Plas et al ., 2020; Pichon et al ., 2022). These weak effects may be due to the following three reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient addition may promote fast communities through shifting intraspecific traits related to fast growth, promoting fast-growing species, or both (Lepš et al ., 2011; Siefert & Ritchie, 2016; Tatarko & Knops, 2018; Zhou et al ., 2018; Pichon et al ., 2022). Additionally, nutrient addition may decrease all stability facets investigated here by decreasing the diversity of slow-fast trait that represents leaf economic spectrum and species richness.…”
Section: Introductionmentioning
confidence: 99%